The Game Maker's Companion - Habgood, Jacob; Nielsen, Nana.; Crossley, Kevin; Rijks, Martin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
The Game Maker's Companion is the long-awaited sequel to The Game Maker's Apprentice. This book picks up where the last book left off, advancing your game development journey with some seriously impressive gaming projects. This time you'll learn how to make professional-quality platform games with solid collision detection and slick control mechanisms and you'll get acquainted with a long-lost icon of platform gaming history on the way. You'll go on to discover techniques to add depth and believability to the characters and stories in your games, including The Monomyth, cut scene storyboarding, and character archetypes. This culminates in the creation of an original atmospheric platform-adventure which will take your GML programming skills to new heights. There's even a handy reference section at the back of the book which will be invaluable for adding common features to your own games. With contributions from four games industry professionals and a highly respected member of the Game Maker community, The Game Maker's Companion is another labor of love that will give you even more hours of enjoyment than the original. If you already own Game Maker, then you really must own this book as well.
Fishpod -- Greetings, Game Maker -- Platform Beginnings: An Idea with Legs -- Zool -- Zool: Taking It to the Nth Dimension -- Empowerment: Sliding Ninjas -- Krool’s Forces: Sweetening the Challenge -- Fighting Talk: the Empower Strikes Back -- Shadows on Deck -- Game Design: “Shadows on Deck” -- Storytelling in Theory -- Storytelling Applied -- Of Mice and Pen: Pirate Art -- GML: From Ninja to Pirate -- Rogues’ Rendezvous: Vertically Sliced -- The Story Begins -- Reference -- Feature Reference.
Keywords: Computer games—Programming.; Computers; Game Development; Computing Milieux